Prevalencia de alteraciones en la visión cromática de pintores expuestos a solventes orgánicos. Municipio de Guarne, 2020. - López Vergara, Danis Beatriz; Escobar Gutiérrez, Ever Mauricio (Universidad Antonio Nariño, 2021)
The Paint industry uses chemical substances as organic solvents to obtain the paint’s raw material, in this way, generating a good material quality. The mentioned before, organic solvents, usually get adhere to the brain tissue, the myelin and the adipose tissue, which make it potentialy neuro-toxic as has been said in numerous investigations. Among the initial signs that can occur we can find; the acquired chromatic changes, which still being a subject of study in our country. Goal: Determinate the prevalence of alterations in the color visión from painters that have been exposed to an Industry’s organic solvents located in Guarne, 2020. Materials and Methods: Descriptive study of a transversal cut with a stadistical sample of 11 painters from the metallurgy industry exposed to organic solvents, which were evaluated using an optometric examination and later an assessment from the visión to the color using the fansworth and Ishihara Tests.